IMPACT OF PSYCHOLOGICAL CHARACTERISTICS ON THE BUSINESS PERFORMANCE OF MUSLIM WOMEN ENTREPRENEURS IN SRI LANKA - M. A. C. Salfiya Ummah (Bank Indonesia, 2021)
Women entrepreneurship is a highly stressful initiative which requires mental efforts related to psychological characteristics. In some Islamic families, women are less empowered, as their mobility is constrained and certain traditions and values observed by society affect their achievement in business. Therefore, this study aims to investigate the effects of several psychological capital (PC) factors on the business performance (BP) of Muslim women entrepreneurs (MWEs) in Sri Lanka. The measurement of PC entails the factors of need for achievement (NA), risk taking (RT), internal locus of control (ILC), and independent motives (IM). Data were collected using a structured questionnaire; the study sample involved 260 MWEs from Sri Lanka’s Eastern Province selected via the simple random sampling technique. The structural equation modeling (SEM) method with AMOS was used to test the proposed hypotheses. The findings show that only RT had a significant and positive impact on BP, whereas NA, ILC, and IM did not significantly influence the BP of MWEs in Sri Lanka. In short, those who were risk takers were able to make positive achievements in their business ventures. The study findings provide evidence of the significance of family members, spouses and social stigma on MWEs’ psychological state and ultimately their business performance.